2018
DOI: 10.1021/acs.jpcb.8b02304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Oxidants on the First Steps of Polydopamine Formation: A Thermodynamic Approach

Abstract: We present a general thermodynamic top-down analysis of the effects of oxidants and pH on dopamine oxidation and cyclization, supplemented with UV–vis and electrochemical studies. The model is applicable to other catecholamines and various experimental conditions. The results show that the decisive physicochemical parameters in autoxidation are the pK values of the semiquinone and the amino group in the oxidized quinone. Addition of Ce(IV) or Fe(III) enhances dopamine oxidation in acidic media in aerobic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
167
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 84 publications
14
167
0
3
Order By: Relevance
“…Bernsmann et al have shown that the presence of stoichiometric excess of Cu 2+ ions in Tris buffer at pH 4.5 resulted in an increase in coating thickness of >70 nm which was difficult to achieve by conventional Tris-HCl route wherein the thickness did not increase beyond 45 ± 5 nm [17]. When compared to copper ions, the presence of other transition metal ions such as Fe 3+ and Ce 4+ has also been shown to accelerate the pDA coating under weakly acidic conditions [18]. Park et al reported the pDA coating under neutral pH by adding fourfold stoichiometric excess of vanadyl (VO 2+ ) ions to the dopamine solution.…”
Section: Accelerating the Coating Speed Of Pda Coatingsmentioning
confidence: 99%
“…Bernsmann et al have shown that the presence of stoichiometric excess of Cu 2+ ions in Tris buffer at pH 4.5 resulted in an increase in coating thickness of >70 nm which was difficult to achieve by conventional Tris-HCl route wherein the thickness did not increase beyond 45 ± 5 nm [17]. When compared to copper ions, the presence of other transition metal ions such as Fe 3+ and Ce 4+ has also been shown to accelerate the pDA coating under weakly acidic conditions [18]. Park et al reported the pDA coating under neutral pH by adding fourfold stoichiometric excess of vanadyl (VO 2+ ) ions to the dopamine solution.…”
Section: Accelerating the Coating Speed Of Pda Coatingsmentioning
confidence: 99%
“…Sodium periodate initiated polymerization of dopamine, and l ‐DOPA in pure MilliQ water was used to avoid buffer salts, which are known to destabilize colloidal NDs . In addition, this method provides faster deposition times than polymerization in alkaline buffers further reducing ND aggregation. In contrast to the well‐established dopamine surface polymerization, l ‐DOPA provides an additional carboxylic group and poly( l ‐DOPA) coatings exhibit higher hydrophilicity than polydopamine .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on the kinetic behaviour of dopamine autoxidation have been carried out. [30][31][32] The summary of these kinetic studies suggest that the autoxidation of dopamine is strongly pH-dependent with the rate of autoxidation faster at higher pH. 32 The increase in rate is due to the abundance of hydroxide ions which are required in the intramolecular Michael addition step.…”
mentioning
confidence: 99%
“…Babbit, Lloyd and more recently Salomäki et al report the rate constant for the formation of aminochrome is first order. 30,31,33 At low pH, the Michael addition is the rate limiting step. 30 If we are able to control the rate of dopamine oxidation, we should be able to control the gelation kinetics of self-assembly.…”
mentioning
confidence: 99%
See 1 more Smart Citation